PERANCANGAN APLIKASI KODE POS INDONESIA BERBASIS MOBILE DENGAN MENERAPAKAN ALGORITMA ZHU-TAKAOKA - Sinambela, Zulhan Sentoso; Ginting, Guidio Leonarde; Ginting, Permanan; Waruwu, Fince Tinus (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Postal code is an official marker element in a region in a country. The postal code was originally only used for the purpose of facilitating work at the post office to sort letters. The general public uses a lot of postal codes to do things like sending goods from one area to another through the post office service, shopping online through the official website, in that activity they are required to fill in the zip code of their destination address or shipping address. In the settlement the author uses the Zhu-Takaoka Algorithm, Zhu-Takaoka is a modified algorithm of the Boyer-Moore algorithm. Algorithm Zhu-Takaoka uses a two-dimensional array to calculate the value of the shift and do the matching from right to left. The design that is expected later this Indonesian postal code application can run well in all devices and Android smartphone versions, and this designed application is also expected to be able to help the general public in finding accurate zip codes by region.Â Keywords: Postal Code Indonesia, Android, Zhu-Takaoka